Nutritional Needs in Mental Healthcare: Study Protocol of a Prospective Analytic Observational Study Assessing Nutritional Status, Eating Behavior and Barriers to Healthy Eating in Psychiatric Inpatients and Outpatients Compared to Healthy Adults - Hotzy, Florian; Risch, Ladina; Mötteli, Sonja (Frontiers in Psychiatry, 2022)
Background Mental disorders are often associated with unhealthy eating behaviours and metabolic comorbidities. This can result in reduced life expectancy and poorer quality of life in people with mental disorders. This study protocol describes an observational study that examines the nutritional status and eating behaviours of people with severe mental illness (SMI) and the need for psychiatric treatment who were between 18 and 65 years old. In addition, the study focuses on possible barriers for healthy eating that have not yet been examined in this population. Methods A total of 192 study participants will be recruited: 64 inpatients and 64 outpatients from the Psychiatric Hospital of the University of Zurich with SMI as well as 64 healthy individuals from the general population as a control group. The participants will be interviewed regarding their nutritional status, eating behaviour, nutrition knowledge, food and cooking skills, personality, attitudes and feelings towards nutrition. In addition, the severity of symptoms and several control variables (e.g., sociodemographic variables and physical activity) will be assessed. For the patient samples, data will comprise routine medical data, and, if available, routine laboratory data. Inpatients will be interviewed once at the beginning of their treatment. Outpatients will be interviewed at the beginning and after 3 months of treatment (same interview questions). Healthy adults of the control group will be interviewed once at any time during the recruitment period. Discussion The described study will identify nutritional needs and possible barriers to healthy eating in patients with mental disorders. The results will help to define recommendations for nutritional risk screening in psychiatric patients and for planning effective nutritional interventions.